Effects of NaCl on water characteristics of heat-induced gels made from chicken breast proteins treated by isoelectric solubilization/precipitation. Issue 1 (2nd January 2016) - Shao, Jun-Jie; Zou, Yu-Feng; Xu, Xing-Lian; Zhou, Guang-Hong; Sun, Jing-Xin
Abstract : Effects of NaCl contents (0%, 0.5%, 1%, 1.5%, and 2%) on texture, water-holding capacities and microstructures of heat-induced gels made from chicken breast meat proteins isolated by isoelectric solubilization/precipitation (ISPC-gels) were investigated. The water characteristics during heating were also elucidated by low-field nuclear magnetic resonance T2 relaxometry. The ISPC-gels with increased NaCl content exhibited good texture and low cooking loss but high centrifugal loss. The amount of free water (T22 component) that was converted into immobilized water (T21 component) increased with NaCl addition in accordance with the decline in cooking loss. However, increased T21 values at 1.5% and 2% NaCl content indicated that water was weakly bound to the macromolecules and was highly mobile. These results were strongly corroborated by microstructure images that illustrated ISPC-gels containing 1% NaCl showed a continuous and dense structure with small pores and thin cross-linked strands, which had the lowest total water loss.